Enhanced CO2 Adsorption and Selectivity of CO2/N2 on Amino-MIL-53(Al) Synthesized by Polar Co-solvents - Abid, H.; Rada, Z.; Duan, Xiaoguang; Sun, Hongqi; Wang, Shaobin (American Chemical Society, 2018)
Amino-MIL-53(Al) was solvothermally synthesized using co-solvents, such as methanol (M), ethanol (E), methanol/acetic acid (MA), or ethanol/acetic acid (EA), as modulators with dimethylformamide (D). The effects of co-solvents on physicochemical properties of amino-MIL-53(Al) were investigated. It was found that the addition of co-solvents in the synthesis leads to the reduction of crystallinity and crystal size of the samples. The textural properties, such as specific surface area and porous structure, were manipulated. Amino-MIL-53-DMA exhibited the highest Brunauer-Emmett-Teller surface area of 632 m 2 /g as a result of the loss of the bridging hydroxyl group, while amino-MIL-53, amino-MIL-53-DE, amino-MIL-53-DEA, and amino-MIL-53-DM presented the surface areas of 400, 356, 321, and 348 m 2 /g, respectively. However, the primary amine groups were maintained on the surface of all of the amino-MIL-53 samples. The co-solvents enhanced CO 2 adsorption on modified amino-MIL-53. CO 2 adsorption capacities on amino-MIL-53, amino-MIL-53-DM, amino-MIL-53-DE, amino-MIL-53-DEA, and amino-MIL-53-DMA are 48, 71, 67, 54, and 75 cm 3 /g, respectively, at standard conditions (1 atm and 273 K). CO 2 adsorption heat could be reduced to 24 kJ/mol on amino-MIL-53-DMA, giving it as a promising adsorbent for carbon dioxide storage at ambient conditions. Besides, the selectivity of CO 2 /N 2 on amino-MIL-53-DEA and amino-MIL-53-DE demonstrates an unprecedentedly separating factor of 637 at 1 atm and 273 K, whereas the separating factors of CO 2 /N 2 on amino-MIL-53, amino-MIL-53-DMA, and amino-MIL-53-DM are only 43, 43, and 153, respectively. Amino-MIL-53-DEA and amino-MIL-53-DE impressively outperform other MOFs and exhibit as an auspicious adsorbent for CO 2 /N 2 separation.